2018
DOI: 10.1177/1932296817750401
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study Validating Select Research-Grade and Consumer-Based Wearables Throughout a Range of Dynamic Exercise Intensities in Persons With and Without Type 1 Diabetes: A Novel Approach

Abstract: Overall, our study demonstrates that current research-grade wearable technologies operate within a ~10% error for both HR and EE during a wide range of dynamic exercise intensities. This level of accuracy for emerging research-grade instruments is considered both clinically and practically acceptable for research-based or consumer use. In conclusion, research-grade wearable technology that uses EE kilocalories · minute and HR reliably differentiates PA intensities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…However, recently a study concluded that wearables have acceptable accuracy regarding monitoring of heart rate and energy expenditures. Thus, wearables may be important in the future as exercise then could be evaluated along with carbohydrate intake, insulin doses and glucose values …”
Section: Exercise Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recently a study concluded that wearables have acceptable accuracy regarding monitoring of heart rate and energy expenditures. Thus, wearables may be important in the future as exercise then could be evaluated along with carbohydrate intake, insulin doses and glucose values …”
Section: Exercise Monitoringmentioning
confidence: 99%
“…Thus, wearables may be important in the future as exercise then could be evaluated along with carbohydrate intake, insulin doses and glucose values. 119…”
Section: Exercise Monitoringmentioning
confidence: 99%
“…Wearable devices can also be used to monitor the PR of individuals undergoing cardiac rehabilitation [162] and for diabetes management [163].…”
Section: Clinical Trials and Home Use Of Cardiac Monitorsmentioning
confidence: 99%
“…This implies that some of the signals that were estimated from each of the devices using hidden algorithms might not be reproducible from other raw data, e.g., FME was an energy expenditure estimation by the Fitbit device calculated from its sensors, which can differ from implementations in other devices. In a recent study comparing different research and consumer devices, an error range of 10% was found for heart rate and energy expenditure measurements [20].…”
Section: Discussionmentioning
confidence: 99%